2021
DOI: 10.3389/fimmu.2021.762598
|View full text |Cite
|
Sign up to set email alerts
|

A Pan-Cancer Analysis of SMARCA4 Alterations in Human Cancers

Abstract: BackgroundSMARCA4, the essential ATPase subunit of SWI/SNF chromatin remodeling complex, regulates transcription through the control of chromatin structure and is increasingly thought to play significant roles in human cancers. This study aims to explore the potential role of SMARCA4 with a view to providing insights on pathologic mechanisms implicated here.MethodsThe potential roles of SMARCA4 in different tumors were explored based on The Cancer Genome Atlas (TCGA), Genotype-tissue expression (GTEx), Tumor I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 24 publications
2
38
1
Order By: Relevance
“…SOX4 increases breast cancer cell viability, migration, and invasion in vitro, and enhances tumor growth and metastasis in vivo [ 50 ]. SMARCA4 is closely related to tumor immune evasion [ 52 ]. HDAC3 is strongly expressed in a subgroup with more aggressive breast cancer [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOX4 increases breast cancer cell viability, migration, and invasion in vitro, and enhances tumor growth and metastasis in vivo [ 50 ]. SMARCA4 is closely related to tumor immune evasion [ 52 ]. HDAC3 is strongly expressed in a subgroup with more aggressive breast cancer [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in agreement with previous findings that demonstrated a role for OLFM4 in promoting tumour cell adhesion and migration [ 9 ]. We detected activation of SMARCA4, a chromatin binding protein that is associated with tumorigenesis in a variety of tissues [ 45 ]. As SMARCA4 expression is negatively associated with CD8 + T cell infiltration of tumours [ 45 ], it has been suggested to control the magnitude and duration of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We detected activation of SMARCA4, a chromatin binding protein that is associated with tumorigenesis in a variety of tissues [ 45 ]. As SMARCA4 expression is negatively associated with CD8 + T cell infiltration of tumours [ 45 ], it has been suggested to control the magnitude and duration of inflammation. In addition, OLFM4 stimulation was predicted to activate TLR4 signalling that is an important regulator of inflammation during cutaneous wound healing [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant correlation between abnormal SWI/SNF subunit and MSI-H, and both are related to PD-L1 expression, high tumor genome mutation rate, and high TIL, resulting in high tumor immune activity. There are several hypotheses regarding the causal affiliation of the two: 1) SWI/SNF complex subunit gene mutations may be caused by MSI; 2) the two may be a reflection of genome-wide hypermethylation, that is, a CpG island methylation phenotype; and 3) SWI/SNF complex deficiency leads to impaired MMR, mutation or MLH1 promoter methylation and epigenetic alterations ( 20 , 21 ). Studies have found that SWI/SNF subunit ARID1A deficiency attenuates mismatch repair (MMR) capacity, impairs mismatch repair in a variety of cancers, leads to genomic alterations in microsatellite instability ( 22 , 23 ), increases TMB, increases neoantigen presentation, increases TILs, and makes tumors susceptible to immune checkpoint blockade.…”
Section: Discussionmentioning
confidence: 99%